Green Banking and Competitive Advantage: A Strategic Management Perspective - Sri Eka Sadriatwi; Mella Katrina Sari (Maneggio, 2025)
This study examines the strategic role of green banking in creating competitive advantage within the banking sector from a strategic management perspective. Using a quantitative approach, this research employs Structural Equation Modeling with Partial Least Squares (SEM–PLS) to analyze data collected from 210 managerial-level employees of commercial banks operating in Indonesia. The findings indicate that green banking has a positive and significant effect on competitive advantage, both directly and indirectly through strategic efficiency as a partial mediating variable. This result suggests that green banking contributes to competitive advantage not merely through regulatory compliance or reputational signaling, but through its integration into core strategic and operational processes. Strategic efficiency, reflected in process optimization, long-term cost reduction, and sustainable innovation, strengthens the effectiveness of green banking in generating superior competitive outcomes. These findings position green banking as a strategic capability that enhances organizational competitiveness when embedded within long-term strategic orientation. This study contributes to the strategic management and sustainability literature by providing empirical evidence from an emerging economy context and by clarifying the internal mechanisms through which green banking creates value. The results offer important implications for banking management in designing sustainability-driven strategies that support long-term competitive advantage